2022
DOI: 10.1002/path.6016
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating tumour DNA after neoadjuvant chemoradiotherapy in patients with locally advanced oesophageal cancer

Abstract: Active surveillance instead of standard surgery after neoadjuvant chemoradiotherapy (nCRT) has been proposed for patients with oesophageal cancer. Circulating tumour DNA (ctDNA) may be used to facilitate selection of patients for surgery. We show that detection of ctDNA after nCRT seems highly suggestive of major residual disease. Tumour biopsies and blood samples were taken before, and 6 and 12 weeks after, nCRT. Biopsies were analysed with regular targeted next‐generation sequencing (NGS). Circulating cell‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 33 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…In a tissue informed panel-based EAC sequencing study (n = 78), several complete responders were also positive at baseline, in line with our findings [8]. Several studies have found that ctDNA dynamics of EAC patients predicts pathological response to neoadjuvant therapy [10,11,27]. For example, non-clearance of ctDNA pre-surgery is associated with an incomplete response [10,11].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In a tissue informed panel-based EAC sequencing study (n = 78), several complete responders were also positive at baseline, in line with our findings [8]. Several studies have found that ctDNA dynamics of EAC patients predicts pathological response to neoadjuvant therapy [10,11,27]. For example, non-clearance of ctDNA pre-surgery is associated with an incomplete response [10,11].…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have found that ctDNA dynamics of EAC patients predicts pathological response to neoadjuvant therapy [10,11,27]. For example, non‐clearance of ctDNA pre‐surgery is associated with an incomplete response [10,11]. Our results also showed that tracking mutations is specific for an incomplete response but the number of positive classified patients was limited.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Nineteen studies reported on the PFS of the ctDNA [14,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. As the range of HR between these studies was 1.21 to 18.70, a significant association was observed between ctDNA-positivity in EC patients and the poorer PFS.…”
Section: Correlation Between Ctdna and Pfsmentioning
confidence: 99%